Chromatographic immunoassays: strategies and recent developments in the analysis of drugs and biological agents. (November 2015) - Matsuda, Ryan; Rodriguez, Elliott; Suresh, Doddavenkatanna; Hage, David S
A chromatographic immunoassay is a technique in which an antibody or antibody-related agent is used as part of a chromatographic system for the isolation or measurement of a specific target. Various binding agents, detection methods, supports and assay formats have been developed for this group of methods, and applications have been reported that range from drugs, hormones and herbicides to peptides, proteins and bacteria. This review discusses the general principles and applications of chromatographic immunoassays, with an emphasis being given to methods and formats that have been developed for the analysis of drugs and biological agents. The relative advantages or limitations of each format are discussed. Recent developments and research in this field, as well as possible future directions, are also considered.